Primary Pulmonary Undifferentiated Pleomorphic Sarcoma: A Rare Malignant Lung Tumor - Do Kyun Kang MD; Min Kyun Kang MD; Woon Heo MD; Youn-Ho Hwang MD, PhD; Ji Yeon Kim MD (SAGE Publishing, 2021)
We report a case of a 56-year-old man with persistent right upper lobe cavitary mass. A chest computed tomography scan showed about 4-cm-sized mass with internal low attenuation and peripheral enhancement in right upper lobe apical segment. The lesion size increased over 1 month. Right upper lobectomy was performed with the intention to treat the lesion. Pathological examination showed primary pulmonary undifferentiated pleomorphic sarcoma. We describe this rare lung disease to remind that primary pulmonary undifferentiated pleomorphic sarcoma could be the differential diagnosis of pulmonary cavitary mass lesions.